Phytoremediation potential of water spinach, ipomoea aquatic and aquaponic farming system in improving water quality of heavy metals contaminated water resources - Mohamad Azam, Ramly (2016)
Water spinach, ipomoea aquatic which is grows largely in Southeast Asia, Southern China and India may contain heavy metals that come from their surroundings habitats. This study was conducted to determine the concentration of the heavy metals contain in water sample and water spinach sample after growing it in the aquaponic system for 50 days. The study also about the phytoremediation potential of water spinach, ipomoea aquatic in restoring water quality of heavy metals contaminated water resources. Two system of aquaponic system were built and using two different type of water which was one using normal water and one from the lake of Universiti Malaysia Pahang (UMP), Pekan Campus which contained metals such as Barium (Ba), Antimony (Sb) and Lead (Pb). To study the capability the water spinach, the plant been collected, dried, grinded and undergo wet digestion process before did the sample analysis. The presence of Lead (Pb) in water spinach sample showed that the plant is actually can absorb the metals contaminated in water sources instead of soil and actually the aquaponic system help in findings the relation in close scale farming system. The results also shows that, for industrial site and manufacturing site mostly is dangerous place to grows plants for consuming by people but suitable as a tools to clean up the nature that environmental friendly.